The legal and accounting environment of the non-profit organisations of China - Zhang, Qi; Lei, Lei; Brown, Alistair (School of Business Law, Curtin Business School, Curtin University of Technology, 2011)
This paper examines how the Chinese centrally planned legal/accounting environment associated with a non-profit sector facilitates the maintenance of tight government control in a rules-based setting. This study also shows how the legal milieu organises civil society and normalises the processes of Chinese not-for-profit services, particularly through state regulations and the use of accounting information. It appears that strict legislation on the accounting regulations and administration of Chinese not-for-profit organisations has the potential to compromise the activities and independence of not-for-profit organisations.